PERCEIVED IMPACT OF THE COVID-19 PANDEMIC ON ELEMENTARY PUPILS SCIENCE ACHIEVEMENT IN NIGERIA - Emmanuel Chibuike NWUNE; Charles Amaechi ANIDI; Emmanuel Nkemakolam OKWUDUBA (Social Sciences and Education Research Review)
The study investigated perceived impact of the COVID-19 pandemic on elementary pupils' science achievement. Five research questions and five hypotheses guided the study. The study made use of the survey research design. The research was done in Awka South Local Government Area of Anambra State. The sample of the study constituted of 300 primary six pupils. The instrument titled 'Perceived Impact of the COVID-19 Pandemic Lockdown Questionnaire (PICPLQ)' was used for data collection. The statistical mean and standard deviation was used for answering the research questions while the independent t-test at 0.05 level of significance was used for testing the hypotheses. The major findings from the study showed that the COVID-19 pandemic impacted the primary school pupils in the area of the time spent in learning, learning motivation and parental support but had no impact on their pressure/stress signs and ways of interaction. Also, the differences in the perceived impact of the COVID-19 pandemic on male and female primary school pupils in the discussed areas were found not to be significant except for their pressure/stress signs. It was recommended among other things that government should provide training for both the teachers and the pupils of primary schools on the proper and effective use of online learning media/platforms in case of another lockdown/outbreak of any disease.